A comprehensive review of barriers to a functional Zakat system in Nigeria: what needs to be done? - Saad, Ram Al Jaffri; Farouk, Abubakar Umar (Emerald Publishing Limited, 2019)
Purpose: Muslims in Nigeria, like in many Muslim-majority countries, are striving to have a functional Zakat system in search of solutions to the perennial problem of poverty and its damning consequences. Nevertheless, there are still unsettled concerns arising from the current and widespread implementation of dissimilar (diverse) approaches to the Zakat system in various parts of the country. The purpose of this paper is to review comprehensively what are the hindrances of a vibrant Zakat system and how far the identified impediments may affect the system in the Nigerian context.Design/methodology/approach:The methodology adopted is the review of extant relevant literature in the field of scholarly publications.Findings: The findings of this study revealed that the fragmented implementation of the Zakat system within the context of the Nigerian democratic system of government lead to the weak governance with respect to law, administration and management; lack of a generally accepted fatwa from the Muslims scholars (Ulamas); absence of Zakat accounting standard; and low compliance behavior are the major barriers that require the attention of government and other stakeholders such as the traditional leaders, the accounting regulatory bodies, the Ulamas, as well as the economic and accounting researchers.Practical implications: It was recommended that the stakeholders should make concerted efforts toward ensuring success of the Zakat system for attaining salvation in the hereafter and for social security, as well as economic prosperity. Originality/value: The paper is the first paper that comprehensively reviews previous literature in the Zakat environment on factors that become barriers to implement a comprehensive Zakat system in Nigeria.